Gastrointestinal and Liver Histopathology in Confirmed SARS-CoV-2 Patients: A Case Series - Geramizadeh, Bita; Yazdanparast, Maryam; Mahboobi, Hamidreza (The International Journal of Gastroenterology and Hepatology Diseases, 2024)
Background and ObjectivesThe COVID-19 pandemic, primarily affecting the respiratory system, has raised questions about its impact on the gastrointestinal (GI) system and liver. Current literature highlights a knowledge gap in understanding the intricate effects of COVID-19 on these organs. This study aims to investigate gastrointestinal and liver histopathology in confirmed SARS-CoV-2 patients.MethodologyA retrospective study was conducted in 2022, examining pathology slides from 37 COVID-19 patients at Namazi and Abu-Ali Sina hospitals in Shiraz, Iran. The sample population comprised all of the cases (37 patients) with confirmed COVID-19 and any type of GI pathology sample for histopathology during the study period. Data included demographics, comorbidities, symptoms, and pathology findings.ResultsThe study revealed a diverse comorbidity landscape, with 45.9% having no comorbidities. Gastritis was prevalent (54.1%), accompanied by ulceration (8.1%) and mucosal edema (21.6%). Among the patients studied, four underwent liver biopsies. The pathological findings from these biopsies included cirrhosis, autoimmune hepatitis, chronic inflammation and fibrosis, and microvesicular glycogenosis.ConclusionGastrointestinal and liver histopathologies in COVID-19 patients were heterogeneous and nonspecific, possibly influenced by comorbidities. Given the potential of SARS-CoV-2 to infect the enterocytes and hepatocytes and the possible involvement of other factors, such as drugs, ischemia, or preexisting conditions, in the gastrointestinal and liver injury of COVID-19 patients, more research is warranted to better understand the pathogenesis and clinical implications of these findings.
Keywords: gastritis